Fabrication of Cu2O nanoparticles with different structures by using block copolymers as capping agent. Issue 181 (13th June 2017) - Li, Na; Li, Wenting; Zhao, Jiaxu; Zhang, Xiaokai; Li, Xue; Li, Chunsheng
ABSTRACT: Different structures of Cu2 O nanoparticles (NPs) were synthesized by using poly(2-vinylpyridine) - b -poly(ethylene oxide) (P2VP- b -PEO) block copolymers as capping agent. The method involve the complextion of P2VP- b -PEO with Cu(NO3 )2 and then reduction of Cu 2+ to Cu2 O by hydrazine hydrate. By adjusting the molar ratio of hydrazine hydrate to Cu 2+ (MR), hollow spheres, solid spheres, cubes and octahedron can be fabricated. However, when Au NPs are used as seeds for Cu2 O formation, Au-Cu2 O core-shell NPs were obtained and the MR have little effect on the morphology of Cu2 O nanostructures. The prepared Cu2 O NPs with different structures may find applications in solar energy photovoltaics and photocatalysis.